Coupled effects of crystallographic orientation and void shape on ductile failure initiation using a CPFE framework. (10th March 2023) - Zhu, J.C.; Ben Bettaieb, M.; Abed-Meraim, F.; Huang, M.S.; Li, Z.H.
Highlights: The studied anisotropic effects are induced by combination of crystallographic orientations and void shapes. Combined anisotropic effects on competition between void coalescence and plastic strain localization are studied. Plastic strain localization is predicted by bifurcation theory at homogenized scale. Combined anisotropic effects play an important role in ductile failure initiation. Abstract: Ductile failure reveals to be an anisotropic phenomenon, for which the proper mechanism has not been clearly addressed yet in the literature. In this paper, the effects of some key anisotropy factors on ductile failure initiation, detected by void coalescence and plastic strain localization, are investigated using unit-cell computations based on crystal plasticity finite element method. The studied anisotropic effects are induced by the combination of initial crystallographic orientations and void shapes. Therefore, single crystals with three different initial orientations and polycrystalline aggregates with three different initial crystallographic textures are respectively considered. A single void with either spherical, prolate or oblate shape is assumed to be preexisting at the center of each unit cell. By contrast to previous analyses in the literature, plastic strain localization is predicted in the present study on the basis of bifurcation theory. To cover a wide range of stress states, the simulations are performed under two macroscopic loading configurations: proportional triaxial stressing, characterized by constant stress triaxiality and Lode parameter, and proportional in-plane straining, specified by constant strain-path ratio. The obtained results show that the combined anisotropic effects play an important role in the occurrence of void coalescence and plastic strain localization, as well as in the competition between them.